2011
DOI: 10.1590/s1413-35552011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty in the elderly: impact on functional performance

Abstract: Objectives: To compare gait and functional performance parameters in elderly subjects who had or had not total hip arthroplasty (THA). Methods: Our sample comprised 23 elderly subjects (72±6.5 years of age) with a mean of 2.6±1.3 years following THA, named the arthroplasty group (AG) and 23 asymptomatic elderly subjects (70.1±5.9 years of age), named the control group (CG). Case and control subjects were paired by gender, age, body mass index and level of physical activity. The GAITRite ® system was used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
3
18
1
1
Order By: Relevance
“…We found that women with hip endoprostheses had a significantly reduced physical performance during fast walking as indicated by the gait parameters velocity and step length. These findings are somewhat different from a case-control study by Guedes et al [21], in which 23 subjects with hip arthroplasties differed significantly from their 23 controls in velocity on all walking tasks (usual, fast, slow and dual-task), but not in cadence. However, these data might be difficult to compare as the study by Guedes et al was based on a convenience sample and did not analyze sex-specific differences.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We found that women with hip endoprostheses had a significantly reduced physical performance during fast walking as indicated by the gait parameters velocity and step length. These findings are somewhat different from a case-control study by Guedes et al [21], in which 23 subjects with hip arthroplasties differed significantly from their 23 controls in velocity on all walking tasks (usual, fast, slow and dual-task), but not in cadence. However, these data might be difficult to compare as the study by Guedes et al was based on a convenience sample and did not analyze sex-specific differences.…”
Section: Discussioncontrasting
confidence: 97%
“…Previous studies assessing gait variables with an electronic walkway mat often did not take account of the impact of endoprostheses although gait patterns have been described to be significantly affected in those patients [11,12,13], and only very few studies have used the GAITRite system to describe gait patterns among persons with knee or hip endoprostheses [21,22]. We found that women with hip endoprostheses had a significantly reduced physical performance during fast walking as indicated by the gait parameters velocity and step length.…”
Section: Discussionmentioning
confidence: 99%
“…It is also related to functional activities, such as crossing the street [19]. A recently published study confirmed our results of lower gait speed in subjects with a total joint replacement [19].…”
Section: Discussionsupporting
confidence: 86%
“…Gait speed is considered to be an important predictor of functional status and adverse health events [18, 19]. It is also related to functional activities, such as crossing the street [19].…”
Section: Discussionmentioning
confidence: 99%
“…Total kalça artroplastisini takiben ameliyat sonrası dönemde yürüme parametrelerinde iyileşme sağlansa da kontrol grubuna kıyasla yürüme parametrelerindeki sapma veya bozuklukların devam ettiği çalışmalarda bildirilmektedir. [13,14] Bunlar içerisinde yürüme hızı, en sık ve kolay değerlendirilen yürüme parametrelerinden biri olup fonksiyonel hareketlerin devamı, günlük yaşam aktivitelerindeki bağımsızlık, düşme riski ve aktivite korkusu ile iliş-kili olması açısından da önemlidir. [13] Obez ve yaşlı bireylerde fonksiyonel kapasitelerindeki gerilemelere bağlı olarak yürüme hızı ve sallanma fazında obez olmayanlara kıyasla azalma meydana gelmektedir.…”
Section: Discussionunclassified